Meio social e surdez: um estudo sobre trajetória sócio-educacional no município de Tocantinópolis-TO - Silva, Maria José dos Santos (2011)
The present study aims at investigating and analyzing, in a geographical space previously determined, how the journey of deaf teenagers has been formed considering familiar, social and cultural aspects that are part of their lives. This research presents an approach that is essentially qualitative, although quantitative data has been used. Five deaf people from a small town in the countryside of Tocantins state were selected, since it is considered as a small-sized town and has a very particular social organization. The data were collected through semi-structured interviews, daily activities observation and school documents from the research participants. As a guiding tool to the data organization, the investigation was based on the cultural and social concepts developed by Pierre Bourdieu (1975, 1997, 2000 e 2005), such as the special education studies developed by Bueno (1998, 1999, 2007); Soares (1990, 1996); Mendonça (2007) and Ferrari (2010) who have their points of view arising from the fact that deafness, definitely serves as a symbol to characterize this population, however, these social identities and trajectories are also formed through the social and cultural relationships established in every social space. In other words, the meaning of the social practices and relationships that the participants have kept is related not only to age, gender, social positions and social-geographical space questions, but also to their condition of being deaf